Influence of zero gravity on germination, growth, development and phenotype variation in Impatiens balsamia - Nhựt, Dương Tấn; Anh, Nguyễn Thị Thùy; Tuấn, Nguyễn Xuân; Nam, Nguyễn Bá; Luận, Vũ Quốc; Huy, Nguyễn Phúc (Vietnam Journal of Biotechnology, 2016)
A general strategy for de novo breeding technique using zero gravity has been emerging in some countries with developed space systems including Russia, the United States of America, China and Japan. In 2011, the first Kibo-ABC programme - "Asian Seeds" - began. Seeds from plants collected in Vietnam, Indonesia, Malaysia, and Thailand including Impatiens balsamia, Antirrhinum majus, and Salvia splendens Ker-Gawl. seed collected by Tay Nguyen Institute for Scientific Research staff were transported to Kibo and then returned to the Earth after a few months. In the present study, germination, growth and development and phenotypic variation of the Impatiens balsamia “zero gravity seeds” were compared with seeds that were not transported into space. Five months after the sowing date, the results indicated that the germination rate of the zero gravity seeds were 2 times higher than the control (22.9% and 9%, respectively). There was no significant difference in some growth and development parameters including plant height, number of branches per plant, leaf diameter, stem diameter and chlorophyll content between the zero gravity seeds and the control. Interestingly, Impatiens balsamia zero gravity seeds derived plants bloomed 16 - 23 days earlier than the control. A few “zero gravity seed” seedlings, however, showed not only lower growth and development abilities than those of the control but also some phenotypic variations such as loss of apex, under-developed apex, unusually large leaf, loss of growth and development and axillary bud formation on internodes, or double petals. This result will be an important prerequisite for the study of plant breeding in space technology - a new way of breeding industry in Vietnam.